2009
DOI: 10.1111/j.1365-2915.2008.00784.x
|View full text |Cite
|
Sign up to set email alerts
|

Population structure and geographical subdivision of theLeishmania majorvectorPhlebotomus papatasias revealed by microsatellite variation

Abstract: Multi-locus microsatellite typing (MLMT) has been employed to infer the population structure of Phlebotomus papatasi (Scopoli) (Diptera: Psychodidae) sandflies and assign individuals to populations. Phlebotomus papatasi sandflies were collected from 35 sites in 15 countries. A total of 188 P. papatasi individuals were typed using five microsatellite loci, resulting in 113 different genotypes. Unique microsatellite signatures were observed for some of the populations analysed. Comparable results were obtained w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
29
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(33 citation statements)
references
References 54 publications
4
29
0
Order By: Relevance
“…Marzouki and others12 performed experiments using a Tunisian strain of P. papatasi but performed identifications using the same approximate database of protein sequences. It follows logically that our MS analysis yielded matches with higher degrees of confidence compared with the study by Marzouki and others,12 which used a population of differential phylogenetic origin42 from the common protein database. Abdeladhim and others41 recently performed an exhaustive analysis of the Tunisian strain P. papatasi salivary proteome through translated Basic Local Alignment Search Tool (BLAST) alignments of RNA transcripts to the same common protein sequence database.…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…Marzouki and others12 performed experiments using a Tunisian strain of P. papatasi but performed identifications using the same approximate database of protein sequences. It follows logically that our MS analysis yielded matches with higher degrees of confidence compared with the study by Marzouki and others,12 which used a population of differential phylogenetic origin42 from the common protein database. Abdeladhim and others41 recently performed an exhaustive analysis of the Tunisian strain P. papatasi salivary proteome through translated Basic Local Alignment Search Tool (BLAST) alignments of RNA transcripts to the same common protein sequence database.…”
Section: Discussionmentioning
confidence: 61%
“…Marzouki and others12 found that the majority of their donors exhibited positive reactivity to salivary proteins at ∼12, 15, 21, 28, 30, 36, and 44 kDa. Sand fly vectors in Tunisia are phylogenetically distinct from sand flies endemic to Egypt, Jordan, and Israel, which are part of a separate, albeit somewhat heterogeneous, population 42. The laboratory-reared P. papatasi used in the present study originated from Israel.…”
Section: Discussionmentioning
confidence: 99%
“…Genetic analyses indicates that, in comparison to L. longipalpis P. papatasi is genetically homogeneous throughout its geographical range [10,51,52] although other evidence suggests a more heterogenous population substructure [53]. If all P. papatasi are reproductively compatible, they probably produce similar signals and there would be no requirement for complex audio signals during copulation, or for populations to produce different sex pheromones, as occurs in L. longipalpis [54].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, it was also shown a correlation between genetic diversity of L. major parasites and their geographic origin [21], [22]. This relationship (geographic dependence) was explained by the genetic diversity of parasite vectors [39] and/or rodent reservoir species present in study areas. It should be noted that these assumptions have never been verified previously.…”
Section: Discussionmentioning
confidence: 79%